1994
DOI: 10.1104/pp.106.2.723
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Acidification and Secondary Metabolite Production in Different Plant Cell Suspensions (A Comparative Study)

Abstract: In this study, a correlation is described between low cytoplasmic pH, measured with the fluorescent probes 2',7'-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein (acetoxymethyl ester) and bis-[3-propyl-5-oxoisoxazol-4-yl]pentamethine oxonol, and the production of secondary metabolites for several plant cell-suspension systems. Anthraquinone production in Morinda citrifolia suspensions is negligible in the presence of 2,4-dichlorophenoxyacetic acid (2,4-D), whereas with naphthalene acetic acid (NAA) a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…For example, in the case of the M. citrifolia cell culture, high concentrations of NAA reduced the production of anthraquinone (Zenk et al 1975). On the other hand, the production of anthraquinone was induced by NAA and inhibited by 2,4-D in the same species (Hagendoorn et al 1994). They observed that, in cultures treated with high concentrations of NAA, concomitant alkalization occurred in the cytoplasm, leading to cell death and a subsequent drop in metabolite accumulation.…”
Section: Auxin Type and Concentrationmentioning
confidence: 94%
“…For example, in the case of the M. citrifolia cell culture, high concentrations of NAA reduced the production of anthraquinone (Zenk et al 1975). On the other hand, the production of anthraquinone was induced by NAA and inhibited by 2,4-D in the same species (Hagendoorn et al 1994). They observed that, in cultures treated with high concentrations of NAA, concomitant alkalization occurred in the cytoplasm, leading to cell death and a subsequent drop in metabolite accumulation.…”
Section: Auxin Type and Concentrationmentioning
confidence: 94%
“…According to Hagendoorn et al (1994), cytoplasmic acidification does not constitute a secondary messenger, but might be a part of the metabolic shift responsible for the production of secondary metabolites following the treatment with elicitors.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured parsley cells, the cytoplasmic pH decreased upon treatment with a Phytophthora megasperma preparation and the pH shift has been correlated with activation of a hydroxylase acting in the synthesis of lignin (Kneusel et al 1989). Using¯uorescent probes, a correlation between secondary metabolite production and a low cytoplasmic pH was observed for three plant species (Hagendoorn et al 1994). Recently, a technique based on the distribution of [ 14 C]benzoic acid between the intracellular and extracellular compartments was used to explore elicitor-induced pH changes in a variety of conditions.…”
Section: Introductionmentioning
confidence: 92%